IMPLEMENTATION OF GOOD CORPORATE GOVERNANCE ON PERFORMANCE OF EMPLOYEES IN HOSPITAL X - HOSNI MUBARAK, MUHAMMAD; AL HIJRAH, MUH FAUZAR; HERIYATI; TAUFIK PAGE, MUHAMMAD; KANDACONG, RIKA KURNIA; RUDIANTY BATTER, SHERLY RUDIANTY BATTER (International Journal of Multidisciplinary Research and Studies, 2022)
The implementation of good corporate governance is very important in improving the quality of work of employees in a hospital. This study aims to provide an overview of the implementation of good corporate governance in improving the quality of employee performance in hospital agencies. The research design used a cross-sectional approach. This research was conducted at a hospital; the sample in this study was 120 employees. The research instrument used a questionnaire. Bi-variate data analysis with chi-square test and simple regression test and path test analysis. The results show that the good corporate governance variable has a positive effect on employee performance at Hospital X with a p-value of 0.018 <0.05, the results of path analysis also show that the correlation of the good corporate governance variable to the performance variable is 0.303 which means that good corporate governance has a contribution to increasing. Quality of work of employees.